The Effect of the Decision in McCracken v Melbourne Storm Rugby League Football Club on Professional Sport in Western Australia - Sadler, Pauline; Yorke, Cameron; Bowyer, Kyle (Curtin University of Technology, 2006)
The 2005 NSW decision of McCracken v Melbourne Storm Rugby League Football Club generated much interest as it appeared to circumvent the provisions of the Civil Liability Act 2002 (NSW), the main purpose of which is to impose a cap on damages awards for personal injury claims and to place limitations on liability in negligence. Western Australia has the Civil Liability Act 2002 (WA), but the relevant section is slightly different to that of the NSW legislation. The purpose of this paper is to examine whether the McCracken case would be likely to be decided in the same way in Western Australia. If so, the administrators, clubs and players involved in professional sport in this jurisdiction should be mindful of the implications, such as the potential for more litigation as a result of injuries sustained in the course of play, or an increase in insurance premiums.